(untitled) (Research, Society and Development, 2022)
Systemic arterial hypertension (SAH) is an important public health problem and when not treated properly can cause serious complications. The lack of control of hypertension results mainly from non-adherence to treatment. This study aimed to know the aspects that influenced the adherence to antihypertensive therapy of people followed in an outpatient health unit. This is a descriptive study with a qualitative approach conducted with 15 adult users of an outpatient clinic in the city of Salvador-BA. The collection of data was given through a semi-structured interview and the data were analyzed by thematic analysis. Two categories emerged from the analysis of the statements: Aspects that hinder adherence; and Aspects that favor adherence. In the first category was the therapeutic scheme, amount of drugs, side effects, financial conditions, the difficulty of access to the drug, lack of knowledge of the disease, therapy as well as forgetfulness. The second category includes predisposition to self-care, knowledge of the disease and therapy, feelings of fear of death and complications, participation of professionals, and family members, and ease of access to medicines. It is concluded that adherence to antihypertensives is a complex issue because it is influenced by several aspects: some negatively influencing while others collaborating for better adherence. Understanding the factors that interfere with adherence is useful for better care and more effective control of the disease.